Lessons for the Relationship of Philosophy and Science From the Legacy of Henri Bergson. (3rd March 2016) - Riggio, Adam
Abstract : One of the many narratives of twentieth century philosophy regards the relationship of philosophy to science: the opinions and arguments over whether philosophy as a discipline should be an assistant, critic, or master over science, and what particular ways philosophy could articulate these roles. One can interpret most of the major conflicts and disciplinary divisions of philosophy as having to do with its relationship with science. The conceptual roots of the general acceptability of a convergence of science and metaphysics would appear to lie in the focus of both subjects, broadly conceived: investigating the nature of existence. Yet, after the rise of post-modernism in many humanities fields, dialogue between philosophy and science on many important issues has become impossible, scientifically-minded intellectuals having no expectation that humanities can contribute usefully to the disciplines of science.